Mediastinal Shift Angle in Fetal MRI Is Associated With Prognosis, Severity, and Cardiac Underdevelopment in Left Congenital Diaphragmatic Hernia - Wang, Xueyao; Shi, Qi; Pan, Weihua; Wang, Weipeng; Wu, Wenjie; Liu, Ming; Xie, Wei; Wang, Xinyun; Wang, Jun (Frontiers in Pediatrics, 2022)
Objective: Fetal MRI has played an essential role in the evaluation and management of congenital diaphragmatic hernia (CDH). We aimed to investigate whether the mediastinal shift angle (MSA) value was associated with the prognosis and the severity of left CDH and explore the relationship between the MSA value and fetal and neonatal cardiac structures and functions. Methods: From January 2012 to December 2020, the fetal MSA values of left CDH in our institution were retrospectively measured. Other prenatal parameters and clinical outcomes of them are collected. We also measured the fetal and postnatal echocardiography parameters to analyze linear correlation with MSA values. Results: A total of 94 patients with left CDH were included. MSA was significantly higher in the deceased group than in the survived group (((38.3±4.7)° vs 32.3±5.3)°, p<0.001). The MSA value of the high-risk defect group (CDH Study Group (CDHSG) C/D type) was significantly higher than that of the low-risk defect group (CDHSG A/B type) ((36.0±4.9)° vs (30.1±4.8)°, p<0.001). The AUC for severity was 0.766 (95% CI, 0.661–0.851, p<0.0001) and the best cut-off value for MSA was 30.7°. Higher MSA correlates with decreased fetal Z-score of left ventricle (LV) width, the diameter of the mitral valve (MV), peak velocity of MV and tricuspid valve (TV), and neonatal LV end-diastolic diameter (LVEDD) and velocity of tricuspid regurgitation (TR) (p<0.05). Conclusion: A high MSA value can effectively predict high-risk defects and high mortality of left CDH. The higher the MSA value, the worse the neonatal conditions, the respiratory and cardiovascular prognosis. The MSA values could reflect the level of left heart underdevelopment, including decreased dimensions and diastolic dysfunction of the left ventricle.